Profil Asam Amino Isi Burger Dari Kaldu Ikan Tongkol (Euthynnus affinis) Melalui Proses Pemanggangan Dan Pengukusan - Finarti Finarti; Asriani Hasanuddin; Nasmia Nasmia (Mitra Sains, 2018)
This study aims to utilize the waste generated from the oil extraction process tuna burger as fill material and to determine the profile of amino acids by product burger filler material from the fish oil extraction process. The method used in this research was experimental research with t test to test the chemical composition (amino acids, water content, protein content, fat content, and ash content,), treatment with Steam and Bake. Each treatment was repeated two (2) times in order to obtain the number of experimental unit as much as 2 x 2 = 4 experimental units. The results of the amino acid profile of research in the treatment rose grilled with keseluruan total amino acid in the amount of 15.02% was the steamed at 7.27%. for the amino acid histidine to highest in steam treatment that is equal to 1.41% and 4.74% for the bake treatment, and the lowest is at 0:10 Methionine% at treatment steamed and grilled. For parameter prosimat highest water content of 43.08% in the treatment steamed while the lowest was in the amount of 24.59% in the treatment of roast. The highest protein content of 10.91% in the treatment roasted while the lowest is equal to 8.81% on a steam treatment. The highest fat content is equal to 1.63% on a steam treatment, while the lowest was 1.51% on a toasted treatment. The ash content of 3.92%, the highest in the treatment of roast and the lowest 2.88% on a steam treatment.